Accounting Practices in the Golden Era of Sultan Babullah: The Sultanate of Ternate (1570-1583) - Assagaf, Nawira Amalia; Sukoharsono, Eko Ganis; Baridwan, Zaki (Jurnal Dinamika Akuntansi dan Bisnis, 2020)
This study aims to explore the accounting practices and their development during the Ternate Sultanate of Sultan Babullah era (1570-1583). This period is a golden era as the sultanate was expanded from the north of Mindano to the south of Bima and from west of Makassar to the east of Banda. Using document analysis and interviews with the sultanate descent family member and historians as the primary source of data, this study employed ethno archaeological approach. The results revealed that accounting was understood in various types during the era that included economic transactions in traditional markets, the use of money for covering social needs, and taxation mechanisms. The sultanate also developed a well-arranged of taxation system where all types of taxation could be paid not only with money, but also by manpower for the Kadaton (or palace), goods, and kora-kora (or royal fleet).